Self-delivery biomedicine for enhanced photodynamic therapy by feedback promotion of tumor autophagy. (1st March 2023) - Chen, Shao-Yi; Zhao, Lin-Ping; Chen, Zu-Xiao; Huang, Chu-Yu; Kong, Ren-Jiang; Wang, Yu-Qing; Zhang, Da-Wei; Li, Shi-Ying; Ti, Hui-Hui; Cheng, Hong
ABSTRACT: Reactive oxygen species (ROS) generated during photodynamic therapy (PDT) can induce autophagy to protect tumor cell from PDT-induced apoptosis. In this work, a self-delivery autophagy regulator (designated as CeCe) is developed for autophagy promotion sensitized PDT against tumor. Briefly, CeCe is prepared by the assembly of a photosensitizer of chlorin e6 (Ce6) and autophagy promoter of celastrol. By virtue of intermolecular interactions, Ce6 and celastrol are able to self-assemble into nanomedicine with great photodynamic performance and autophagy regulation capacity. Under light irradiation, CeCe would produce ROS in tumor cells to amplify the oxidative stress and promote cell autophagy. As a result, CeCe exhibits an enhanced photo toxicity by inducing autophagic cell death. In vivo experiments indicate that CeCe can predominantly accumulate in tumor tissue for a robust PDT. Moreover, CeCe has a superior therapeutic efficiency compared to monotherapy and combined treatment of Ce6 and celastrol, suggesting a synergistic antitumor effect of PDT and autophagy promotion. This self-delivery nanomedicine may advance the development of the co-delivery nanoplatform to improve the antitumor efficacy of PDT by promoting autophagy. Statement of Significance: Autophagy is a "double-edged sword" in cellular homeostasis and metabolism, which can promote tumor progression but also induce an unknown impact on tumor inhibition. In this work, a self-delivery autophagy regulator (designated as CeCe) was developed for autophagy promotion sensitized photodynamic therapy (PDT). By virtue of intermolecular interactions, Ce6 and celastrol were found to self-assemble into stable CeCe without drug excipients, which exhibited great photodynamic performance and autophagy regulation capacity. In vitro and in vivo findings demonstrated a superior tumor suppression ability of CeCe over the monotherapy as well as the combined treatment of Ce6 and celastrol, suggesting a synergistic antitumor efficacy by PDT and autophagy promotion. Graphical Abstract: Image, graphical abstract